2014
DOI: 10.1021/es500351e
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Trace Organic Contaminants in Open-Water Unit Process Treatment Wetlands

Abstract: The bottoms of shallow, open-water wetland cells are rapidly colonized by a biomat consisting of an assemblage of photosynthetic and heterotrophic microorganisms. To assess the contribution of biotransformation in this biomat to the overall attenuation of trace organic contaminants, transformation rates of test compounds measured in microcosms were compared with attenuation rates measured in a pilot-scale system. The biomat in the pilot-scale system was composed of diatoms (Staurosira construens) and a bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 58 publications
6
102
0
Order By: Relevance
“…The wetland contained three baffles to promote plug-flow hydraulic conditions, and was lined with concrete and geotextile fabric to prevent the growth of emergent macrophytes. A 2e10-cm deep, porous, diffuse biomat composed of algae (mainly diatoms), associated heterotrophic microbes, and detritus accumulated on the wetland bottom (Jasper et al, 2014a). During the day, photosynthesis at the biomat surface increased the concentration of dissolved oxygen throughout the water column.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wetland contained three baffles to promote plug-flow hydraulic conditions, and was lined with concrete and geotextile fabric to prevent the growth of emergent macrophytes. A 2e10-cm deep, porous, diffuse biomat composed of algae (mainly diatoms), associated heterotrophic microbes, and detritus accumulated on the wetland bottom (Jasper et al, 2014a). During the day, photosynthesis at the biomat surface increased the concentration of dissolved oxygen throughout the water column.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were conducted in August and October 2012, and June 2014. Due to the small percentage of water that was estimated to be lost via evaporation (7.3 ± 1.1%; Jasper et al, 2014a), no water was added during the course of the in-situ batch experiments. The observed, first-order inactivation rate constants of indigenous wastewater bacteria in the in-situ batch reactors were calculated from linear regression of ln(C t /C 0 ) versus time (k B obs , h À1 ).…”
Section: Experiments With In-situ Batch Reactors At the Open-water Wementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to removal of nutrients, they are also being investigated and designed for the removal of organic contaminants by sorption, biotransformation and photolysis . Several reports have described degradation rates, mechanisms and types of microbes involved in degradation, often determined in laboratory or small scale microcosm systems . The identification of degradation products formed by biotransformation and phototransformation is less predictable than human metabolism …”
Section: Introductionmentioning
confidence: 99%
“…Biological activity in the biomat causes diurnal cycling due to competing photosynthetic and heterotrophic processes with oxygen supersaturation in the water column during the day and suboxic conditions at night. The microorganisms that colonized this system were initially investigated in Jasper et al (26) and shown to contain a high abundance of a single species of diatom, Staurosira construens var. venter, in conjunction with a diverse bacterial community.…”
mentioning
confidence: 99%